PEMANFAATAN LINGKUNGAN SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA - Tiara Nita Rozanah Rachman (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
Learning in the classroom is often seen as boring. This is one of the causes of low student learning activities. Effective learning needs to be supported by the use of adequate learning media. The use of the environment as a learning media is carried out by involving students and teachers. This activity seeks so that students can play an active role in the teaching and learning process. The environment is very influential on the teaching and learning process for students, because the environment used as a learning media in the educational process can provide a positive experience for students. By utilizing the environment, students will feel happy and become more active in exploring their knowledge, and teaching and learning activities will not feel boring. Keyword: Utilization of the environment, learning media, experience